2022
DOI: 10.30684/etj.v40i7.2270
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of a Window Solar Air Collector with Moveable Absorber Plates

Abstract:  A new novel window with 7 movable absorber plates with different opening angles.  Best thermal performance and minimum of sunlight were obtained at angle 0 .  Lower thermal performance and maximum of sunlight were obtained at angle 90 .  A flexibility between hot air and sunlight requirements for angles between 0 and 90 .Window solar air collector is an imperative instrument for heating residential buildings in cold regions. This paper presents a numerical investigation of the thermal performance of a win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Solar energy is a very large, inexhaustible source of energy, moreover, using solar energy instead of fossil fuels reduces CO2 emissions and thus reduces global warming [1]. Solar energy can be transformed into electricity by a solar photovoltaic panel or to thermal energy by a solar collector to use for many purposes [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy is a very large, inexhaustible source of energy, moreover, using solar energy instead of fossil fuels reduces CO2 emissions and thus reduces global warming [1]. Solar energy can be transformed into electricity by a solar photovoltaic panel or to thermal energy by a solar collector to use for many purposes [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the thermal heat transfer coefficient for both collectors was evaluated. The results showed that the (air moving down) collector was more efficient than the other one.The performance of air solar collector with a movable absorber panels and glass covers on both sides a numerically has been studied by Dawood et al [8]. The study found that the thermal performance was enhanced by 67% when the plates adjusting to the angle 0.…”
Section: Introductionmentioning
confidence: 99%